(untitled) (Human Factors in Design, 2013)
This study analyzes the method of hand mapping to assess the perceived discomfort during the use of hand tools by different age groups. The aim was to determine the influence of age and how it affects the perception of discomfort. Considering that, this was a study that involves subjective aspects, it seeks to analyze results by means of a comparative assessment among different areas of the hand. Hence, the hand palm was divided by both anatomical and interface criteria for the task. The manual activity consisted in a simulation of opening procedure for PET packaging of soft drinks. The results show differences in perception of discomfort among the ages analyzed. The adopted method contributes to the ergonomic design, as the perception of discomfort is an important parameter in the product design, providing more efficient and accessible products.